Assessing the influence of geographic distance in parasite communities of an exotic lizard - Bezerra, Castiele Holanda; Pinheiro, Luan Tavares; Melo, Gabriela Cavalcante De; Zanchi-Silva, Djan; Queiroz, Murilo De Souza [UNESP]; Anjos, Luciano Alves Dos [UNESP]; Harris, David James; Borges-Nojosa, Diva Maria (Springer Nature, 2016)
The decay of similarity between biological communities with increasing geographical distance is a well-established pattern in ecology, but there are more complex factors acting on host population connections that influence this association for parasite communities, such as parasites' colonization ability and degree of connectivity between host populations. Here we aim to determine the helminth communities associated with different populations of the host lizard Hemidactylus mabouia, testing if the similarity of parasite communities decreases as the distance between them increases. For this, we collected samples of lizard populations in seven sites from Northeastern coast of Brazil and identified parasite species of helminths and pentastomids in each host, calculated the Sørensen indices of presence/absence and abundance of each pair of communities and related them to the geographical distance. We did not find a relationship of decaying similarity with increasing distance between the parasite communities of the host populations. This can be explained by factors such as the characteristics of the contact between the host populations, and by modes of transmission of most parasite species. Furthermore, it may be related to the exotic nature of the host in Brazil so that parasite communities have not reached equilibrium.
Keywords: Helminths; Hemidactylus mabouia; parasite ecology; species turnover